2016
DOI: 10.1111/jeb.12868
|View full text |Cite
|
Sign up to set email alerts
|

Hidden genetic variation in the germline genome of Tetrahymena thermophila

Abstract: Genome architecture varies greatly among eukaryotes. This diversity may profoundly affect the origin and maintenance of genetic variation within a population. Ciliates are microbial eukaryotes with unusual genome features, such as separation of germline and somatic genomes within a single cell and amotitic division. These features have previously been proposed to increase the rate of molecular evolution in these species. Here, we assessed the fitness effects of genetic variation in the two genomes of natural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…While others have argued that laboratory cultures should have low levels of heritable genetic variation (DeLong et al, 2014), T. pyriformis has mechanisms to maintain larger than expected levels of genetic variation (Dimond & Zufall, 2016). Because of this, and to assess whether observed changes in body size were more likely due to plasticity or rapid evolution, we fitted two possible models that track change in the abundance and average body size of a population, N , as it grows logistically towards a carrying capacity K with intrinsic growth rate r .…”
Section: Methodsmentioning
confidence: 99%
“…While others have argued that laboratory cultures should have low levels of heritable genetic variation (DeLong et al, 2014), T. pyriformis has mechanisms to maintain larger than expected levels of genetic variation (Dimond & Zufall, 2016). Because of this, and to assess whether observed changes in body size were more likely due to plasticity or rapid evolution, we fitted two possible models that track change in the abundance and average body size of a population, N , as it grows logistically towards a carrying capacity K with intrinsic growth rate r .…”
Section: Methodsmentioning
confidence: 99%
“…While others have argued that laboratory cultures should have low levels of heritable genetic variation (DeLong, Hanley & Vasseur 2014), T. pyriformis has mechanisms to maintain larger than expected levels of genetic variation (Dimond & Zufall 2016). Because of this, and to assess whether observed changes in body size were more likely due to plasticity or rapid evolution, we fitted two possible models that track change in the abundance and average body size of a population, N , as it grows logistically towards a carrying capacity K with intrinsic growth rate r .…”
Section: Methodsmentioning
confidence: 99%
“…Yet, our results very clearly indicate a strong increase in growth rates with genetic diversity that weakens at warmer temperatures (Figure 2a). One possible explanation for the observed increase in population growth with genetic diversity is the occurrence of heterosis, or outbreeding enhancement, which has not been ruled out in this particular system (Dimond & Zufall, 2016). Indeed, clonal lines from different genetic backgrounds may also belong to different mating types, which could have led to increasing levels of sexual reproduction and heterozygosity in genetically diverse combinations.…”
Section: Discussionmentioning
confidence: 92%
“…While increasing genetic diversity resulting in higher population growth is common in other systems (Frankham, 2005), it is not clear why that should be the case in this particular study system. Previous work has indicated that inbreeding depression-that is, a decrease in absolute fitness (or intrinsic growth rate) with increasing levels of inbreeding (often due to the accumulation of deleterious alleles)-is unlikely to happen in T. thermophila (Dimond & Zufall, 2016), and outbreeding depression-that is, the decrease in absolute fitness due to the arrival of maladapted alleles-is also unlikely (Dimond & Zufall, 2016). Yet, our results very clearly indicate a strong increase in growth rates with genetic diversity that weakens at warmer temperatures (Figure 2a).…”
Section: Discussionmentioning
confidence: 99%